Performance Evaluation of Inductive Miner for Internship Program Workflow - Afina Lina Nurlaili; Muhsin Muhsin; Dhian Satria Yudha Kartika (Jurnal Mantik, 2021)
Modern organizations involve a high number of activities in their operations, which can be very complex. Process model is used to simplify these complex activities. Various algorithms for discovering process models have been developed in process mining. Process mining can extract important information from each activity in obtained cases. There are three process mining algorithms commonly used: Alpha, Heuristic Miner, and Inductive Miner. Each of the algorithms has its own characteristics. This paper compares these algorithms for the Internship Program. Based on the obtained evaluation, Alpha algorithm can't describe the process based on PKL event log well. It is because loop processes exist. It is also shown that the PKL process is not implementing the SOP well yet. On the other hand, Heuristic Miner neglects minor processes which do not frequently happen and does not describe it in the process model. Inductive miner combines the working principle of Alpha Miner and Heuristic Miner. Overall, the process model that is formed uses the Alpha algorithm which is closest to reality because it has a fitness of 0.96.